A CASE STUDY ON STUDENTS’ REASONS FOR NOT SWITCHING ON THEIR CAMERAS DURING ONLINE CLASS SESSIONS - Bernadette Tobi; Wan Hurani Osman; Anna Lynn Abu Bakar; Irma Wani Othman (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The COVID-19 pandemic has brought academic face-to-face classes to a halt, globally. Schools, higher institutions, and all learning centres were forced into emergency mode searching for platforms to ensure the continuity of teaching and learning (UNESCO, 2020). Online classes were made mandatory, and instructors curated lessons to best deliver their lessons. However, frustrations emerged where teachers shared their experience of talking to the abyss of their computer screens as students did not switch on their cameras during online lessons. A link to a Google form questionnaire which is quantitative (questionnaire), qualitative (short answer questions) in nature was given to the author’s communicative English class students. Fifty students in an English communicative course responded and the chairperson of the course was interviewed (qualitative) to find challenges teachers faced in their online classes. The author focused on one issue - students’ refusal to turn on their cameras. The findings revealed the main reasons for not turning on the cameras during lessons as lack of internet data, poor internet connection, social norms, not being physically presentable, and not being comfortable to be looked at by peers. Instructions from teachers and class assessments affect students’ choice to turn on the camera, too. These findings serve as knowledge contributions for teachers to understand students and to do content curation.